Visualizations of urban space : digital age, aesthetics, and politics - Wagner, Christiane (Professor of aesthetics) (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This book explores environments where art, imagination, and creative practice meet urban spaces at the point where they connect to the digital world. It investigates relationships between urban visualizations, aesthetics, and politics in the context of new technologies, and social and urban challenges toward the Sustainable Development Goals. Responding to questions stemming from critical theory, the book focuses on an interdisciplinary actualization of technological developments and social challenges. It demonstrates how art, architecture, and design can transform culture, society, and nature through artistic and cultural achievements, integration, and new developments. The book begins with the theoretical framework of social aesthetics theories before discussing global contemporary visual culture and technological evolution. Across the twelve chapters, it looks at how architecture and design play significant roles in causing and solving complex environmental transformations in the digital turn. By fostering transdisciplinary encounters between architecture, design, visual arts, and cinematography, this book presents different theoretical approaches to how the arts' interplay with the environment responds to the logic of the constructions of reality. This book will appeal to scholars, researchers, and upper-level students in aesthetics, philosophy, visual cultural studies, communication studies, and media studies with a particular interest in socio-political and environmental discussions"--
Foreword / by Morton Schoolman -- Cultural Images: Real and Imagined Experiences -- Urban Space and Collective Consciousness -- The Arts and Traces of the Ideal City -- Democratization of Art and Culture -- Visual Media Effects -- Urban Resilience: Toward Postcolonial Aesthetics -- Sociopolitical Facts, Art, and Technology -- Technicization and Aestheticization of Social and Urban Structures -- The Urban Image in Motion and Connection -- The Arts' Function: Social Inclusion and Sustainability -- Designing for Sustainability -- Aesthetic, Social, and Urban Solutions for a New World View.
Keywords: City planning; Art and cities; Sociology, Urban; Aesthetics -- Social aspects; ART / Criticism; ART / Popular Culture; NATURE / Ecology